Scenery by M. V. Dobuzhinsky as a Version of Pushkin Studies - Markov, Alexander (Literatūra, 2020)
The sets by M. V. Dobuzhinsky for the operas by Mussorgsky and Tchaikovsky based on Pushkin’s works represent an attempt to reconstruct Pushkin’s world and Pushkin’s attitude to history. The libretto required a stylization and standardization of scenography, but Dobuzhinsky continued to interpret the images of St. Petersburg and central Russia, correlating the plots of operas with a new national upsurge. Thus, the plot of The Queen of Spades was understood as part of Pushkin’s view on the successes and failures of the Petrine reforms, about the connection between adventurism and the imperial style, which corresponded to the general cultural myth of Petersburg but was supplemented by a number of observations on the Pushkin text. The plot of Boris Godunov was read not as a Russian story, but as a common one for countries inheriting the Polish-Lithuanian Commonwealth and Russia. The plot of Eugene Onegin was brought closer to the dacha plots of Russian literature, becoming part of the integrated image of a lost Russia. It is proved that Dobuzhinsky in his decisions followed not the structure of the libretto, but a close reading of Pushkin’s texts.
Keywords: Dobuzhinsky; Pushkin; Tchaikovsky; Musorgsky; scenography; decoration; сlose reading; illustration; pictorial interpretation